Modelling of a hydraulic system coupled with lumped masses. Issue 1 (31st December 2022) - Treml, Paul; Mikota, Gudrun; Manhartsgruber, Bernhard; Brandl, Andreas
ABSTRACT: A coupled hydraulic-mechanical system with a lumped parametric mechanical part has been set up, measured and mathematically modelled in the frequency domain. The main focus of this article is the identification of unknown system parameters, which depends on the models of coupling and dissipation. The set-up under investigation can be excited hydraulically, by flow rate, or mechanically, by force. The responding pressures of the hydraulic subsystem and the accelerations of the mechanical subsystem are measured, from which transfer functions between excitation and system states can be calculated. The property of reciprocity is used for the processing of measurement data. With a suitable two-step strategy and non-linear optimization unknown system parameters can be identified from measurements. Additionally, the agreement of model and measurement and the physical meaningfulness of these parameters are examined. The proposed model succeeds in predicting measured transfer functions, whose data weren't used for the identification of model parameters.